Keterampilan Pemecahan Masalah Siswa Pada Materi Listrik Arus Searah di Masa PJJ - Ken Ayu Citra; Nehru Nehru; Febri Berthalita Pujaningsih; Cicyn Riantoni (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2021)
This study aims to determine the description of students' problem solving skills in direct current electricity in physics subjects which are conducted through Distance Learning (PJJ). This type of research is quantitative research. The research subjects were 26 students of class XII MIPA 7 SMA Negeri 1 Kota Jambi. The data was collected using a direct current electrical problem solving skills test questions consisting of 6 essay questions. The data obtained were analyzed using descriptive statistics. From the results of data analysis, it is known that the lowest score is 14 and the highest score is 46, and the average result of the students' problem solving skills test is 37. Meanwhile, the percentage of each student's problem solving stage is classified as very bad. Thus, it was concluded that the problem solving skills of class XII MIPA 7 students on direct current electricity through PJJ were classified as very low criteria.